2017
DOI: 10.3233/nre-162128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of task specific training and wrist-fingers extension splint on hand joints range of motion and function after stroke

Abstract: The results of this study provide an evidence that task specific training and wrist/fingers extension splint are effective in improving fingers dexterity, upper extremity function and wrist/hand range of motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The results of this study are in line with the results presented by (Khallaf et al, 2017) which stated that exercise increases the range of motion in stroke patients. Furthermore, research (Uswatte et al, 2018) also states that range of motion exercises performed at optimal intensity can increase the range of motion in stroke patients by 2.3 units.…”
Section: Figure 5 Forest Plot Of Range Of Motion Exercise On Range Of...supporting
confidence: 92%
“…The results of this study are in line with the results presented by (Khallaf et al, 2017) which stated that exercise increases the range of motion in stroke patients. Furthermore, research (Uswatte et al, 2018) also states that range of motion exercises performed at optimal intensity can increase the range of motion in stroke patients by 2.3 units.…”
Section: Figure 5 Forest Plot Of Range Of Motion Exercise On Range Of...supporting
confidence: 92%
“…Other studies on ROM exercise interventions reported an increase in the ROM of upper limb extension, but the increase was not significant. 51 However, another finding related to the results of this study is the significant increase in ROM in the upper extremity after exercise therapy interventions, physical therapy, and health education guidance in post-stroke patients, 52,53 so we assume that ROM exercises combined with an educative-supportive approach and mentoring for 7 consecutive days increase the ROM significantly. Another factor that influenced the results of this study is the accuracy and precision of the ROM measurements, in which a study reported significant differences by 3 assessors with different levels of experience and expertise, 54 but in this study, only 1 assessor conducted the measurements.…”
Section: Discussionmentioning
confidence: 62%
“…As older individuals grow in numbers, they will also present with multiple chronic medical conditions. The clinical presentation of some of these conditions includes reduced manual dexterity 1,7,8 . For some patients, inability to care for their remaining teeth or insert and remove their existing RPDs might lead earlier to the decision to extract their remaining teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of some of these conditions includes reduced manual dexterity. 1,7,8 For some patients, inability to care for their remaining teeth or insert and remove their existing RPDs might lead earlier to the decision to extract their remaining teeth. However, tooth loss has been shown to lead to an increased risk of early mortality, as mentioned by Gupta et al 9 In addition, the use of RPDs for tooth replacement has been shown to improve the quality of life of the individual, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%